Prawno-administracyjne uregulowania udzielania ochrony cudzoziemcom na terytorium Polski a stan faktyczny - Hryszkiewicz, Robert (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The author in the presented article introduces legal and administrative regulations for granting protection to foreigners on the territory of Poland. The author does this by analyzing the applicable legal provisions relating to this matter, and also indicates statistical data and examples of the application of the analyzed provisions in practice by the competent administrative authorities. It should be stated that despite very broad and fairly precisely described forms of assistance to foreigners seeking for various reasons protection and seeking assistance in the Republic of Poland, the data provided indicate a decline in the applications for granting asylum or other forms of assistance.
Keywords: the protection of foreigners; administrative authorities; forms of assistance